Cultural dimensions of Indigenous participation in education and training - Dockery, Alfred Michael (Social Science Research Network (online), 2009)
This paper develops empirical measures of Indigenous Australians’ attachment to their traditional cultures, and explores the relationship between culture and participation in VET. The findings reject the notion that Indigenous culture acts as a barrier to achievement in education and training. Rather, it appears attachment to traditional culture fosters improved education and training outcomes, and that Indigenous people access VET for cultural pursuits. However, lower access in remote areas disadvantages Indigenous Australians with stronger cultural attachment. In this sense, Indigenous persons do face a trade-off between cultural aspirations and pursuit of further education and training.